Mergers & Acquisitions : the proposed acquisition of Sonos by Apple - Viegas, André Fortunato Gonçalves do Estanque (2022)
Almost all devices around us today can be defined by two words: “Smart” and “Connected”. Smart speakers are one of the fastest growing categories with these two features. Smart speakers’ market is expected to grow at an impressive double-digit pace in the coming years. Despite of Apple being considered one of the most innovative companies in the world, it is failing to establish a good position in this market. In this dissertation, it is proposed the acquisition of Sonos Inc. by Apple in order to improve its performance in this very attractive market. Sonos Inc. intrinsic value is equal to $5698 million. The deal will be an all-cash deal, following a friendly approach with a purchase premium of 30% on Sonos Inc. current market value as of 31st of August 2021. The proposal generates a total purchase price of $6450 million, capturing net synergies of $1127 million.